A fatal case of severe methaemoglobinemia due to nitrobenzene poisoning. (7th October 2011) - Gupta, Alok; Jain, Nirdesh; Agrawal, Avinash; Khanna, Arjun; Gutch, Manish
Abstract : An acute poisoning with nitrobenzene presenting as methaemoglobinemia is an uncommon medical emergency. A young girl with nitrobenzene induced methaemoglobinaemia died despite use of mechanical ventilator, administration of oral methylene blue and parenteral ascorbic acid. Here author highlights the rare occurrence of such cases, methaemoglobin induced severe oxidative stress, unexplained splenomegaly and leucocytosis and the ineffectivity of oral methylene blue and other supportive measures in evading death due to nitrobenzene poisoning.